Ductile cast irons: microstructure influence on fatigue crack propagation resistance - Francesco Iacoviello; Vittorio Di Cocco; Mauro Cavallini (Fracture and Structural Integrity)
Microstructure influence on fatigue crack propagation resistance in five different ductile cast irons (DCI) was investigated. Four ferrite/pearlite volume fractions were considered, performing fatigue crack propagation tests according to ASTM E647 standard (R equals to 0.1, 0.5 and 0.75, respectively). Results were compared with an austempered DCI. Damaging micromechanisms were investigated according to the following procedures: - “traditional” Scanning Electron Microscope (SEM) fracture surfaces analysis; - SEM fracture surface analysis with 3D quantitative analysis; - SEM longitudinal crack profile analysis - Light Optical Microscope (LOM) transversal crack profile analysis;